Loss of mitofusin 2 links beta‐amyloid‐mediated mitochondrial fragmentation and Cdk5‐induced oxidative stress in neuron cells. (13th January 2015) - Park, Junghyung; Choi, Hoonsung; Min, Ju‐Sik; Kim, Bokyung; Lee, Sang‐Rae; Yun, Jong Won; Choi, Myung‐Sook; Chang, Kyu‐Tae; Lee, Dong‐Seok
Abstract Mitochondrial dysfunction is implicated in age‐related degenerative disorders such as Alzheimer's disease (AD). Maintenance of mitochondrial dynamics is essential for regulating mitochondrial function. Aβ oligomers (AβOs), the typical cause of AD, lead to mitochondrial dysfunction and neuronal loss. AβOs have been shown to induce mitochondrial fragmentation, and their inhibition suppresses mitochondrial dysfunction and neuronal cell death. Oxidative stress is one of the earliest hallmarks of AD. Cyclin‐dependent kinase 5 (Cdk5) may cause oxidative stress by disrupting the antioxidant system, including Prx2. Cdk5 is also regarded as a modulator of mitochondrial fission; however, a precise mechanistic link between Cdk5 and mitochondrial dynamics is lacking. We estimated mitochondrial morphology and alterations in mitochondrial morphology‐related proteins in Neuro‐2a (N2a) cells stably expressing the Swedish mutation of amyloid precursor protein (APP), which is known to increase AβO production. We demonstrated that mitochondrial fragmentation by AβOs accompanies reduced mitofusin 1 and 2 (Mfn1/2) levels. Interestingly, the Cdk5 pathway, including phosphorylation of the Prx2‐related oxidative stress, has been shown to regulate Mfn1 and Mfn2 levels. Furthermore, Mfn2, but not Mfn1, over‐expression significantly inhibits the AβO‐mediated cell death pathway. Therefore, these results indicate that AβO‐mediated oxidative stress triggers mitochondrial fragmentation via decreased Mfn2 expression by activating Cdk5‐induced Prx2 phosphorylation. <boxed-text content-type="graphic" id="jnc12984-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Mitochondrial fragmentation induced by amyloid‐beta oligomer (AβOs) which is generated from the Swedish mutation of amyloid precursor protein (APP) accompanies reduced Mfn1/2 levels. Interestingly, the Cdk5 pathway, including phosphorylation of the Prx2‐related oxidative stress, has been shown to regulate Mfn1/2. Furthermore, Mfn2 over‐expression significantly inhibits the AβO‐mediated neuronal cells death pathway, but not Mfn1 over‐expression. Therefore, these results indicate that AβO‐mediated oxidative stress triggers mitochondrial fragmentation via decreased Mfn2 expression by activating Cdk5‐induced Prx2 phosphorylation. ATP, adenosine triphosphate; Bax, Bcl‐2‐associated X protein; Bcl‐2, B‐cell lymphoma 2; Cdk5, Cyclin‐dependent kinase; Cyt C, cytochrome C; Mfn2, mitofusin 2; Prx2, peroxiredoxin 2; ROS, reactive oxygen species.